Landscape barriers to pollen and seed flow in the dioecious tropical tree Astronium fraxinifolium in Brazilian savannah - Manoel, Ricardo O. [UNESP]; Rossini, Bruno C. [UNESP]; Cornacini, Maiara R. [UNESP]; Moraes, Mário L. T. [UNESP]; Cambuim, Jose [UNESP]; Alcantara, Marcelo A. M. [UNESP]; Silva, Alexandre M. [UNESP]; Sebbenn, Alexandre M.; Marino, Celso L. [UNESP] (Public Library of Science (PLoS), 2021)
Gene flow studies provide information on gene exchange between populations, which is essential for developing genetic conservation strategies. Such analyses enable a better understanding of the life history and seed and pollen dispersal mechanisms of plant species. In this study, we investigate pollen and seed flow in a regenerant population of the pioneer species Astronium fraxinifolium in an area degraded during the construction of a hydroelectric dam. We mapped, sampled, sexed, and genotyped 386 individuals in the regenerant population (RP), as well as 128 adult trees located along two highways adjacent to the degraded area; one in Mato Grosso do Sul State (MS) and other in São Paulo State (SP). Parentage analyses was carried out for 370 individuals of the RP population, using as putative parents 348 individuals from RP and all 128 individuals sampled in MS and SP. Based on parentage analysis and eight microsatellite loci, our analyses revealed that for individuals of the RP with an identified father (pollen donor), 1.1% of the pollen was dispersed up to 532 m, while for those with an identified mother (seed donor), 0.5% of seeds were dispersed up to 4,782 m. However, a large proportion of pollen (76.5%) and seeds (57%) immigrated from trees outside the sampled populations. Pollen and seeds were dispersed through a pattern of isolation by distance. Genetic diversity was significantly similar between adults of both highway populations and individuals from RP, with significant levels of inbreeding detected only in RP. Our results demonstrate that the nearest trees contributed pollen and seeds for the recovery of the degraded area, indicating reproductive spatial isolation among the sampled populations due to the damming of the river. Such results help to understand the process of regeneration for A. fraxinifolium in regenerant populations to inform strategies for conservation and environmental recovery with this species. Copyright: